Evaluación de la calidad microbiológica en función de la norma Inen 2395 en yogures artesanales expendido en la feria de la Plaza Jesús Camañero parroquia matriz del Cantón Alausí. - Arcos Guamán, Talía Manuela (2022)
The intrinsic characteristics of dairy products and their handling favor the presence of etiological microorganisms. To rule out the presence of any of these, a microbiological analysis was carried out, which allowed identifying and quantifying the microorganisms present in the yogurt and determining the hygienic-sanitary quality during the production chain to guarantee the health of consumers. The general objective of the research was the microbiological evaluation of artisanal yogurts sold at the fair that takes place at La Plaza Jesús Camañero of Matriz parish in Alausí canton, based on the Ecuadorian Technical Standard INEN 2395: 2011 which determines the quality microbiological analysis of the product through permissible parameters of good quality levels and acceptable quality levels. Eight brands of artisanal yogurt from the different producers were analyzed for three consecutive weeks, on Sundays, the analysis and count of microorganisms was carried out in the food quality control laboratory of the Technical University of Cotopaxi, for the count of E. coli. /total coliforms was analyzed with 3M Petrifilm Plates, while the count of molds and yeasts was used with Compact Dry YM plates, for the count of lactobacillus it was carried out in the accredited laboratory Ecuachemlab. According to the results obtained, they report that for total coliforms the count exceeds the permissible parameters with values of 1.19 x104 cfu/g and 1.62 x104 cfu/g; for Escherichia coli, 12.5% of the samples analyzed exceed the value established in the regulations with a value of 1.00 x103 cfu/g; for molds and yeasts, it is evident that 87.5% meet the established parameter with a maximum value of 3.7x103 cfu/g and a minimum of 5 cfu/g; in the lactobacillus count, 75% of the yogurts tested met the requirements established in the standard with a minimum value of 20.00x104 cfu/g and a maximum of 22.00x107 cfu/g. It is concluded that 75% of the entire population analyzed, comply with the parameters established in the regulations, however, recommendations are made for that 25% that does not comply with the regulations.